A new process for the recovery of palladium from a spent Pd/TiO2 catalyst through a combination of mild acidic leaching and photodeposition on ZnO nanoparticles. Issue 3 (12th December 2022) - Muscetta, Marica; Pota, Giulio; Vitiello, Giuseppe; Al Jitan, Samar; Palmisano, Giovanni; Andreozzi, Roberto; Marotta, Raffaele; Di Somma, Ilaria
Abstract : A combination of leaching and sacrificial photocatalytic deposition was proposed to recover palladium. The recycling of the photocatalyst resulted in a practical method for reducing wastes generated during the process. Abstract : Currently, palladium represents an expensive and scarce element in the Earth's crust, with the mineral resources of platinum group metals (PGMs) predominately localized in South Africa and Russia. The growing demand for this material necessitates the development of suitable strategies to recover it from end-of-life devices. The recovery of palladium by combining leaching and sacrificial photocatalytic deposition in a low-waste process was proposed here as a possible alternative to the current technologies. The effect of the species involved in the single processes in the recirculated stream was evaluated, where a negligible influence of the sacrificial species (ethanol) in the leaching unit was noticed. Different home-prepared ZnO photocatalysts were tested, and the best performance in terms of recovery of palladium was obtained in the presence of ZnO nanoparticles prepared through sol–gel synthesis. The proposed procedure is a viable route for the recovery of Pd from spent catalysts: by combining the processes, the complete oxidation of palladium was observed in about 15 minutes, while the recovery of Pd through photodeposition on ZnO occurred within 120 minutes of irradiation.